Milano and the role of parks in shaping its recent urban development - Frigerio, Alessandro (International Planning History Society Proceedings, 2024)
In the last decades, Milano has reinvented itself from industrial city to advanced tertiary global capital, more attentive to sustainable development, with a progressive change in the role and nature of planning tools and a controversial redefinition of the balance between public and private sectors in determining urban development through regeneration projects. Parks have a crucial role in this process, and landscape design has increased its importance in urban transformation projects, on the edge between fashionable greenification and the progressive affirmation of an ecological approach that interprets the landscape as a primary and structuring element of the urban and metropolitan sustainable development. A decisive milestone in this planning history, the project “Nine Parks for Milano”, envisaged in 1995 the launch of a broad strategy to restructure the city shape, starting from the configuration of nine urban parks. Moving from a historical overview on park-making in the city, the paper investigates some of the projects that were directly or indirectly generated by the “Nine Parks” vision, discussing planning tools, negotiation processes, design actions, and effective results, reflecting on the combined role of urban and landscape design and planning in shaping more sustainable and resilient metropolitan systems.